A study of Chinese restaurant reverse logistics: Issues and challenges of kitchen waste disposal - Shi, Jingwei (2017)
In recent years, as environmental degradation is increasingly seriously, protecting the environment has also been discussing for a long time. In terms of the catering industry, the ways to dispose of kitchen waste play a significant role in the green recycling process. From the collection, recycling to reprocessing, the operation model is the main part that needs to be analyzed in depth, and the model is also different based on a country’s policies, technology or other factors. In terms of China, the fast economic growth has improved people’s living standards to a large extent, while the standards’ improvement also brings an increasing amount of kitchen waste to people’s daily life.